2013
DOI: 10.1590/s1415-43662013000500006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do lodo de esgoto e do nitrogênio nos fatores produtivos do girassol

Abstract: RESUMO Dentre as diversas alternativas de disposição final de lodo de esgoto no Brasil, o uso agrícola se destaca por sua economicidade e adequação ambiental. Assim, o objetivo deste trabalho foi avaliar o efeito do lodo de esgoto compostado e do N nos parâmetros produtivos do girassol, após a sexta aplicação de lodo de esgoto em diferentes doses. O experimento foi conduzido na Fazenda Experimental São Manuel, SP, pertencente à Faculdade de Ciências Agronômicas da UNESP de Botucatu,SP. Foi adotado o delineamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
5
0
7
Order By: Relevance
“…In the achenes, N accumulation was 1.425 g plant -1 at the dose of 0 m 3 ha -1 and 2.844 g plant -1 at the dose of 136 m 3 ha -1 , corresponding to an increment of 100%. Similar results were reported by Lobo et al (2013), who observed linear increase in N concentration in sunflower achenes as the applied N doses increased.…”
Section: Resultssupporting
confidence: 90%
“…In the achenes, N accumulation was 1.425 g plant -1 at the dose of 0 m 3 ha -1 and 2.844 g plant -1 at the dose of 136 m 3 ha -1 , corresponding to an increment of 100%. Similar results were reported by Lobo et al (2013), who observed linear increase in N concentration in sunflower achenes as the applied N doses increased.…”
Section: Resultssupporting
confidence: 90%
“…Lobo et al (2013) obtiveram, após 6 aplicações de lodo de esgoto nas mesmas doses efetuados neste experimento, os seguintes resultados para o rendimento de óleo na dose de 200% de N que, como fonte de lodo de esgoto, foi superior que o tratamento que recebeu N mineral. Lobo et al (2012) concluíram que a melhor dose de N no girassol do mesmo hibrido utilizado neste experimento foi de 100 kg ha -1 para a produtividade de grão, matéria seca e rendimento de óleo.…”
Section: Resultsunclassified
“…Agricultural crops fertilized with sewage sludge respond satisfactorily: Lobo et al (2013) observed increase in grain yield, oil yield, weight of 1,000 seeds and dry matter yield of sunflower with the application of sewage sludge. In addition, Chiba et al (2008) reported that sewage sludge is an efficient source of nitrogen (N) for sugarcane ratoon and there is no need to complement with N fertilizers in order to obtain the same yields of stem and sugar of a conventional mineral fertilization.…”
Section: Introductionmentioning
confidence: 98%